The Influence of Service Quality on BPJS Employment Participant Satisfaction and Trust - Sri Adrianti Muin; Yusri Yusri; Besse Imrayani Imran; Kasno Kasno (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
This paper examines how service quality affects satisfaction and trust among its participants of BPJS Employment which is the employment insurance agency of the state in Indonesia. Based on SERVQUAL approach, the study decomposes service quality into its five central dimensions, which include; service tangibles, service reliability, service responsiveness, service assurance, and service empathy, and determines their ability to predict satisfaction among the participants. An explanatory quantitative study with a structured questionnaire given to 370 sampled participants was used in the study; the samples had been stratified randomly. Using regression and mediation tests, it can be found that each dimension of service quality has a significant impact on satisfaction and, among them, empathy (beta= 0.242) and responsiveness (beta= 0.226) are the most notable ones. Trust is also majorly affected by satisfaction (beta = 0.456) and the ability of satisfaction as mediator between service quality and trust is confirmed using a Sobel test (z = 5.75, p < 0.001). The results are convincing of the essential roles of emotionally intelligent and participant-service in administration in social welfare institutions whose interpersonal treatment can be more vital than structural efficiency in establishment institutional legitimacy. In addition to verifying existing theories, the present research will provide theoretical progress in the literature on management as it shows the role of satisfaction as the strategic mediator of the process of building trust, not just as the evaluative final state.